2020
DOI: 10.1002/adom.202000743
|View full text |Cite
|
Sign up to set email alerts
|

Graphoepitaxy of Large Scale, Highly Ordered CsPbBr3 Nanowire Array on Muscovite Mica (001) Driven by Surface Reconstructed Grooves

Abstract: Muscovite mica [KAl 2 (Si 3 Al)O 10 (OH) 2 ] is a good electrical and thermal insulator with stable physical and chemical properties. [1] As a layered crystal, bulk muscovite can be compressed into 2D nanosheets by mechanical or chemical exfoliation, which has sparked attention since the emergence of graphene. Few-layered muscovite exhibits useful physical properties, such as excellent proton and electrical conductivity, efficient cations exchange for pollutants, etc. [2-5] Moreover, due to weak interlayer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The mica (001) surface can be further modified by removing the interlayer potassium to induce a distortion of the aluminosilicate tetrahedra, resulting in the breaking of the intrinsic quasi-hexagonal symmetry and the making of groove bunches along the [100] direction. As reported by Li et al, such grooves enabled vapor-phase graphoepitaxial growth on the millimeter-scale, unidirectional single-crystalline CsPbBr 3 NW arrays …”
Section: Growth Methods and Mechanismsmentioning
confidence: 56%
See 1 more Smart Citation
“…The mica (001) surface can be further modified by removing the interlayer potassium to induce a distortion of the aluminosilicate tetrahedra, resulting in the breaking of the intrinsic quasi-hexagonal symmetry and the making of groove bunches along the [100] direction. As reported by Li et al, such grooves enabled vapor-phase graphoepitaxial growth on the millimeter-scale, unidirectional single-crystalline CsPbBr 3 NW arrays …”
Section: Growth Methods and Mechanismsmentioning
confidence: 56%
“…As reported by Li et al, such grooves enabled vapor-phase graphoepitaxial growth on the millimeterscale, unidirectional single-crystalline CsPbBr 3 NW arrays. 125 2.4.2. Vapor-Phase Nonepitaxy Growth.…”
Section: Vapor-phase Growthmentioning
confidence: 99%
“… 22 24 However, most of these studies used unprotected in-plane NWs with horizontal alignment. 12 , 19 28 A few studies have investigated vertically aligned MHP NW arrays, which have been proven to have high light extraction capability for LED devices 14 , 29 and high resolution for pixel image sensors. 30 So far, studies on vertically aligned CsPbBr 3 NW arrays are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of CsPbBr 3 NWs and their various optoelectronic applications have been explored, e.g., for lasing, multicolor displays, control of emission anisotropy, and light guiding as well as photodetection. However, most of these studies used unprotected in-plane NWs with horizontal alignment. , A few studies have investigated vertically aligned MHP NW arrays, which have been proven to have high light extraction capability for LED devices , and high resolution for pixel image sensors . So far, studies on vertically aligned CsPbBr 3 NW arrays are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the synthesis of aligned CsPbBr 3 and CsPbCl 3 nanowires on mica substrates using a vapor-phase van der Waals incommensurate epitaxial method. [67,110] The low lattice mismatch between the exposure surface of CsPbX 3 (Br/ Cl) and mica making the nanowires well aligning along one direction related to mica substrate, as shown in Figure 10a. The photoluminescence anisotropy in as-prepared CsPbBr 3 nanowires was examined under linearly polarized laser excitation, as shown in Figure 10b.…”
Section: Strong Emission Anisotropy In Perovskite Nanowiresmentioning
confidence: 99%